Sand tray therapy for reducing post-traumatic stress disorder (ptsd) and enhancing well-being in children and adolescents - Dharmayanti, Putu Ari; Suranata, Kadek; Rismawan, Kade Sathya Gita; Paramartha, Wayan Eka; Bakar, Abu Yazid Abu; Amat, Saleh (Jurnal Konseling dan Pendidikan, 2025)
Post-Traumatic Stress Disorder (PTSD) is a mental health issues that is commonly experienced by children and adolescents as a result of traumatic events such as natural disasters, social conflicts, and violence. The high prevalence of PTSD among children and adolescents requires further intervention due to the risk of long-term psychological impacts. This study aims to evaluate the effectiveness of Sand Tray Therapy in reducing PTSD symptoms and improving well-being in children and adolescents. The study uses an A-B-A-B experimental design, which is a variation of the single subject design (SSD), involving five subjects who were selected through a screening process and considered as representative of a population with PTSD and low psychological well-being. The research instruments used are the Posttraumatic Stress Disorder Checklist (PCL-5) and Ryff’s Psychological Well-Being Scales (PWB). Data were analyzed using the Wilcoxon Signed-Rank Test to compare PTSD and well-being scores between phases, and Cohen's d was used to measure the effect size of changes between phases. The results of this study indicate that sand tray therapy has a clinically significant positive effect in reducing PTSD symptoms and improving psychological well-being. Thus, this method can be considered an alternative psychological intervention for children and adolescents who suffer from PTSD and require an improvement in psychological well-being.